Giles of Viterbo : the Commentary on the Sentences of Petrus Lombardus. - Nodes, D. (Studies in Medieval and Reformation Traditions, 151., 2010)
The Sentences Commentary of Giles of Viterbo embodies the intellectual and spiritual vision of one of the luminaries of the Italian Renaissance and a reformer of his religious order. Giles strove to locate in ancient wisdom truths revealed in the Bible and Christian doctrine. He composed ""according to Plato's mind, "" but, influenced by Ficino and the revival of theologia Platonica, he integrates material from Greek myth and metaphysics with the Bible and Christian theology. Until now only a small portion of Giles's Commentary has been published, yet this major work contains some of the best e.